Land Subsidence Investigation in Negeri Sila, Nusalaut Island, Using Resistivity Method - Rian Amukti; Abi Dzikri Alghifari; Alexander Yosep Elake; Francy Nendisa; Christian Jacob Souisa (Indonesian Journal on Geoscience, 2022)
DOI:10.17014/ijog.9.2.The phenomenon of land subsidence in Negeri Sila of Nusalaut Island was caused by an earthquake in Ambon Island and surrounding areas on September 26, 2019 with the magnitude of 6.5. This research had been conducted using a resistivity method with a dipole-dipole configuration. Land subsidence occurred due to seawater intrusion around the area. The earthquake around Ambon Island was the trigger, so soil creep occurred.The purpose of this study is to obtain a weak resistivity zone area that indicates subsidence. The results showed a low resistivity value of 1-10 Ohm meters which indicated a weak zone of potential subsidence of the ground surface, and the presence of sea water intrusion into the area.